The crisis of democratic representation in the Andes - Mainwaring, Scott, 1954-; Bejarano, Ana María; Pizarro Leongómez, Eduardo (Stanford University Press, 2006)
This volume analyses and explains the crisis of democratic representation in five Andean countries: Bolivia, Colombia Ecuador, Peru and Venezuela. It addresses an important question for Latin America as well as other parts of the world: why does representation sometimes fail to work?